ONCOPLASTIC RESECTION OF THE MAMMARY GLAND WITH A SLIDING DERMOGLANDULARY FLAP WITH A Z-SHAPED INCISION - E. A. Rasskazova; A. D. Zikiryakhodzhayev; E. K. Saribekyan (Исследования и практика в медицине, 2017)
Oncoplastic resections are a radical surgical treatment for breast cancer, as well as a method for the rehabilitation of patients, since operations are classified as organ preserving. When the tumor node is localized in the upper-inner quadrant of the breast, it is difficult to achieve good aesthetic results. One of the solutions to the problem is the use of a sliding flap with a Z-shaped incision. In P. Hertsen MORI from 2014 to 2016, the operation with the use of a sliding flap was performed in 13 patients. The prevalence of the process, patients were distributed as follows: ТisN0 М0–1, Т1N0 М0–7, Т2N0 М0–3, Т1N1 М0–2 .Molecular subtypes distribution was the following — luminal type A— 8, luminal type B — 3, triple-negative subtype — 1 patient. Localization of the tumor site in the breast: the upper-internal quadrant — 9, upper — 1, lowerinner quadrant — 3 .The upper Zshaped flap was used in 10 patients, the lower Zshaped flap in 3 cases. Postoperative period in all patients was without com plications. The wound healed by primary intention in all patients. Cosmetic effect was good. The observation period is from 6 months to 2 years, the median is 1.1 years. Data for local recurrence and distant metastases were not detected. 2 patients had only surgical treatment, in the remaining 8 cases, radiation therapy with or without drug therapy. In all cases the operation is performed on one breast, correction of the second breast was not required.The article presents the clinical observation of patients with oncoplastic resection of the Zshaped flap, a detailed procedure of the operation.